ASSESSMENT OF THE GENETIC STRUCTURE OF THE CHILD POPULATION IN PRYKARPATTYA ACCORDING TO THE AB0 AND RH BLOOD GROUP ANTIGENS AND DISTRIBUTION DETERMINATION OF GENETIC PREDISPOSITION TO THE DEVELOPMENT OF INTRAUTERINE GROWTH RETARDATION - Кочерга, З. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The genetic structure of the child population of different ethnic groups (Hutsuls, Boikos, Opoliany and Pokuttia) in Ivano-Frankivsk region has been determined according to the distribution of AB0 and Rh blood group antigens carriers. For this purpose, the original medical reports of the children’s out-patient clinics in district centers of the region and in Ivano-Frankivsk city as well as the statistical reporting materials of the organization-methodic department of the regional children’s clinical hospital have been thoroughly analyzed. Taking into account the number of individuals with different phenotypes it became possible to make up the following set with the decrease in number of carriers with different blood groups according to the AB0 system: А(ІІ)>0(І)>В(ІІІ)>АВ(ІV). Among the ethnic groups of Prykarpattya Hutsuls were distinguished by the benefits of phenotypes А(ІІ) and АВ(ІV) as compared to Boikos, Opoliany and Pokuttiany. Analysis of the combination of AB0 and Rh antigen associations proved that children with phenotype А(ІІ) Rh+ (48,32 %) prevailed in the population of the region, children with phenotype 0(І) Rh+(23,41%) took the second position, children with phenotype – В(ІІІ) Rh+(14,33%) were the third. As part of the study it became possible to establish the associations of AB0 and Rh antigens and some multifactorial diseases. The analysis of inheritance regularities of intrauterine growth retardation associated with gender has revealed that in 54% of cases this syndrome was transmitted through the maternal side, in 28% – through the paternal side and in 18% – through both sides. Taking into account the blood group antigens of the AB) system, individuals with АВ (ІV) phenotype appeared among newborns with intrauterine growth retardation 1.80 times more often as compared to healthy newborns (χ²=19.37; р=0,0001). The likelihood of intrauterine growth retardation development was higher in Rh positive male-infants as compared to Rh negative ones. Newborns with 0(І) Rh+ phenotype had significant preference among newborns with IUGR (χ2 =7.47; p=0.006). The highest relative risk of intrauterine growth retardation formation was revealed in 0(І) Rh+ male-infants and 0(І) Rh- female-infants versus АВ (ІV) newborns. Rh positive female newborns with 0(І) and В(ІІІ) phenotypes, as well as Rh negative female newborns with 0(І) phenotype and male newborns who are the carriers of А(ІІ) Rh+ or Rh- and 0(І) Rh- may be resistant to the intrauterine growth retardation development. A prospect for further research in this area is to identify molecular-genetic markers of I intrauterine growth retardation syndrome development.